Inhibitory Power of Moringa Leaf Extract (Moringa oleifera L.) Concentration of 50%, 75% And 100% On Mix Bacterial Growth of Root Canal - Putu Rusmiany; Ilma Yudistian; Benedictya Victoria Soyweru Philippus (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Necrotic teeth can be maintained with root canal treatment, through three critical stages, namely preparation, sterilization, and filling. Sterilization is one of the critical stages that must be carried out during treatment, and it aims to eliminate as many pathogenic microorganisms as possible through irrigation and medicine. In recent times, there have been many studies on the use of traditional medicine from herbal ingredients as a substitute for chemical drugs. This study aims to determine the inhibitory power produced by moringa leaf extract against mixed bacteria in the root canal. Materials and methods: This study is a laboratory study with a Post Test Control Group Design. The sample groups used were mixed bacteria in the root canal which were divided into 5 groups, namely the group with moringa leaf extract treatment with concentrations of 50%, 75%, and 100%, the treatment group given ChKM as a positive control, and the group treated with distilled water as a negative control, with each repetition 5 times. Moringa leaf extraction was carried out using the maceration method using 96% ethanol solvent. Inhibition zone testing was carried out using the Kirby-Bauer method. Results: The inhibitory power produced at a concentration of 50% was obtained on an average of 10.73mm, a concentration of 75% was obtained on an average of 14.24mm, and a concentration of 100% was obtained on an average of 16.48mm. Conclusion: Moringa oleifera L. leaf extract at concentrations of 50%, 75%, and 100% can inhibit the growth of mixed bacteria in the root canal, with the most effective concentration at 100% Moringa oleifera L. leaf extract.